Boar semen: complementary techniques for its evaluation - González, L.O. (2013)
Nuclear parameters of the spermatozoa (morphology, maturation and condensation degree), sperm functional capacity (membrane response to hypoosmotic medium and sperm resistance to heat incubation) and semen quality were evaluated in sixteen healthy, sexually mature and fertile boars. Sperm nuclei were stained with the Feulgen reaction to observe morphology, with Aniline Blue to determine chromatin maturation, and with Toluidine Blue to determine chromatin condensation. The mean percentage and standard error of normal nuclei in each of the three tests was: 96.6±0.8, 98.1±1.1 and 99.6±0.2 respectively. The percentage of sperm with total motility before heat incubation was 62.3±3.9, whereas that of sperm with progressive motility was 35.0±4.6 and that of Hypoosmotic Swelling Test+ (HOS+) cells 53.3±2.5. After heat incubation (Thermoresistance Test), the percentage of sperm with total motility was 37.3±3.5, that of sperm with progressive motility 13.4±3.6, and that of HOS+ cells 37.7±3.5. Nuclear parameters did not correlate significantly between each other or with the other sperm parameters studied. Total motility had correlation with: progressive motility, sperm viability, HOS test and total motility and HOS test after Thermoresistance Test. Consequently, combining different complementary tests would improve estimations of semen boar quality.